Moving forwards, sideways and up in the air: observations on the locomotion of semiterrestrial tadpoles (Cycloramphidae) - Sabbag, Ariadne Fares [UNESP]; Dos Santos Dias, Pedro Henrique; Brasileiro, Cinthia A.; Haddad, Celio F. B. [UNESP]; Wassersug, Richard J. (Oxford Univ Press, 2022)
Semiterrestrial tadpoles live on wet rock surfaces and have evolved independently in at least seven anuran families. They have a flat venter, laterally compressed keratinized jaws and elongated, largely finless tails. When threatened, they can jump. Here, we describe the kinematics of locomotion for semiterrestrial tadpoles of the genera Cycloramphus and Thoropa (Cycloramphidae). Forward locomotion can be accomplished solely by the upper jaw cyclically engaging and disengaging from the substrate. Undulating tail movements, in contrast, cause the tadpoles to move laterally, like sidewinding snakes, rather than forwards. Jumping is an explosive escape behaviour with an unpredictable trajectory. Jumping requires rapid elevation of the head and extension of the torso and tail. This is made possible by epaxial musculature that extends onto the cranium and movement of the tail in the sagittal plane. Tadpoles near metamorphosis extend their hindlimbs symmetrically when jumping, even when the limbs are too small to provide thrust. The rapid rostral elevation of the snout, extension of the trunk and symmetrical extension of the hindlimbs is a kinematic pattern shared with post-metamorphic frogs when they jump. This suggests that semiterrestrial tadpoles use essentially the same neural programme as that used by frogs to jump.
Keywords: anuran larvae; Cycloramphus; jump; sidewind; Thoropa